DAMPAK BULLYING BAGI KALANGAN SISWA SEKOLAH DASAR - Yuyun Elisabeth Patras; Fajar Sidiq (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2017)
The research is a study case, its location in the Ciparigi State Elementary School Bogor, West Java. The focus of this research is the impact of bullying for the social interaction of elementary school students. Data collection technique form is through observation, interviews and documentation. Validity of data examination that used are credibility, transferability, dependability and confirmability. Analysis of data that used is qualitative descriptive. The results were showed that forms of bullying occurs in Ciparigi Elementary School including physical bullying and verbal bullying. As a result, subjects had a impact on the social interaction that makes the subject difficult to interact with the environment because it is always on a bully by the other students. Difficulty interacting is a major problem faced by the subject because the subject becomes not dare to start interacting not only to his friend, but the teachers as well as parents. Conclusions from this research is the impact of bullying on the victim's social interactions at school or outside the school.